Combination antiangiogenic tyrosine kinase inhibition and anti‐PD1 immunotherapy in metastatic renal cell carcinoma: A retrospective analysis of safety, tolerance, and clinical outcomes. (1st March 2021) - Laccetti, Andrew L.; Garmezy, Benjamin; Xiao, Lianchun; Economides, Minas; Venkatesan, Aradhana; Gao, Jianjun; Jonasch, Eric; Corn, Paul; Zurita‐Saavedra, Amado; Brown, Landon C.; Kao, Chester; Kinsey, Emily N.; et al.
Abstract: Introduction: Two separate antiangiogenic tyrosine kinase inhibitors (TKIs) and immunotherapy (IO) combinations are FDA‐approved as front‐line treatment for metastatic renal cell carcinoma (mRCC). Little is known about off‐protocol and post‐front‐line experience with combination TKI–IO approaches. Methods: We conducted a retrospective analysis of mRCC patients who received combination TKI–IO post‐first‐line therapy between November 2015 and January 2019 at MD Anderson Cancer Center and Duke Cancer Institute. Chart review detailed patient characteristics, treatments, toxicity, and survival. Independent radiologists, blinded to clinical data, assessed best radiographic response using RECIST v1.1. Results: We identified 48 mRCC patients for inclusion: median age 65 years, 75.0% clear cell histology, 68.8% IMDC intermediate risk, and median two prior systemic therapies. TKI–IO combinations included nivolumab–cabozantinib (N +C; 24 patients), nivolumab–pazopanib (N+P; 13), nivolumab–axitinib (6), nivolumab–lenvatinib (2), and nivolumab–ipilimumab–cabozantinib (3). The median progression‐free survival was 11.6 months and the median overall survival was not reached. Response data were available in 45 patients: complete response (CR; n = 3, 6.7%), partial response (PR; 20, 44.4%), stable disease (SD; 19, 42.2%), and progressive disease (3, 6.7%). Overall response rate was 51% and disease control rate (CR+PR+SD) was 93%. Only one patient had a grade ≥3 adverse event. Conclusion: To our knowledge, this is the first case series reporting off‐label use of combination TKI–IO for mRCC. TKI–IO combinations, particularly N+P and N+C, are well tolerated and efficacious. Although further prospective research is essential, slow disease progression on IO or TKI monotherapy may be safely controlled with addition of either TKI or IO. Abstract : Real world use of combination anti‐angiogenic tyrosine kinase inhibitor (TKI)—anti‐PD1 immunotherapy (IO) is feasible, well tolerated and efficacious for metastatic renal cell carcinoma in the second line setting and beyond. Although further prospective research is essential to define optimal use of salvage TKI‐IO, slow disease progression on IO or TKI monotherapy may be safely controlled with addition of either a TKI or IO.